Biometry of buffalo (Bubalus bubalis) ovaries in relation to different stages of the oestrous cycle - CHANDRAHASAN, C; RAJASEKARAN, J (The Indian Journal of Animal Reproduction, 2023)
Ovaries from non-descript pluriparous buffaloes collected from slaughter house were grouped into four stages based on the characteristics of the corpus luteum and morphometry of the ovary were recorded during different stages of the oestrous cycle. Follicles were grouped according to the diameter as s. 2, 3-5, 6-10 and >10 mm. Biometry of ovaries on left and right side was not found to differ significantly and also between stages of the cycle. However, length, diameter and weight of the corpus luteum showed high significant difference during the four stages of the cycle. The mean number of visible follicles between right and left ovaries did not differ ssignificantly. The number of follicles of s. 2 mm diameter size increased at two times of the cycle indicating two waves of follicular growth in buffalo ovaries.